Safety and Reliability – Safe Societies in a Changing World 2018
DOI: 10.1201/9781351174664-181
|View full text |Cite
|
Sign up to set email alerts
|

The future of driver training and driver instructor education in Norway with increasing ADAS technology in cars

Abstract: On average, more than two people are killed or severely injured every day in Norway in road traffic. Hence, elements that benefit a decrease in this number will be welcomed, such as "Advanced Driver-Assist System" (ADAS) technology. However, increasing technology in cars might require new driving skills compared to those taught today and the transition to more and new technology could potentially increase the accident rate. In the safety industry, it is well known that training for new and more automated techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Over the past three to four years, there has been a slight increase in scientific literature on how to deal with the new technological solutions in the driver-training industry (Forster et al 2019;Lubkowski et al 2021;Saetren et al 2018). In addition, Manser et al (2019), in a report on driver-training guidelines for automated vehicle technology in the United States, identified five levels of educational requirements for skills and knowledge drivers should be trained on when using advanced driver-assistance systems (ADAS):…”
Section: Teaching Advanced Driver-assistance Technology To Learner Dr...mentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past three to four years, there has been a slight increase in scientific literature on how to deal with the new technological solutions in the driver-training industry (Forster et al 2019;Lubkowski et al 2021;Saetren et al 2018). In addition, Manser et al (2019), in a report on driver-training guidelines for automated vehicle technology in the United States, identified five levels of educational requirements for skills and knowledge drivers should be trained on when using advanced driver-assistance systems (ADAS):…”
Section: Teaching Advanced Driver-assistance Technology To Learner Dr...mentioning
confidence: 99%
“…To identify up-to-date literature on the topic of teaching ADAS technology, we conducted a literature review. We used the Oria and Google Scholar search engines and set the timeframe to the past five years to yield the most recent literature and because little was written on this topic before that (Saetren et al 2018). The search terms were 'teaching automation', 'driver behaviour', 'driver instructor and automated technology', 'driver training and automated technology', and 'advanced driver-assistance systems'.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Cars are rapidly being developed with new advanced automated technology, which can be divided into different levels --from level 0, where the driver performs all operations, to level 5, where the car is fully autonomous, and the person in the car has changed status from driver to passenger (SAE 2021). Research in human factors has revealed that new technological solutions often lead to different human errors and change the risk factors rather than eliminating them (Saetren and Laumann 2015); therefore, it is necessary to consider which new skills and competencies current and future drivers need and how they should be acquired (Saetren et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Even if simulators cannot fully replicate the realworld experience, they offer the researcher an advantage that real-world studies cannot match: the ability to control and repeat experimental conditions and create prescribed scenarios with selected variables [9]. This enables manipulating several variables for revealing different driver responses to dissimilar conditions in a short timeframe, which would be substantially impossible otherwise [8], [10]. The multiple variables influencing drivers' behaviors [11] might be subjective or environmental, that in turn can be temporary and nontemporary [12]; for instance, in the first case, we can assess the driving performance according to age [13] or the effects of alcohol, drugs, and/or fatigue on driving behavior [14], whereas in the second case it is possible to appraise the driving performance in different environmental conditions, such as different types of adverse weather conditions or day/night hours [15].…”
Section: Introductionmentioning
confidence: 99%